PENGARUH KETERLIBATAN MANAGER DALAM PEMILIHAN INISIATIF STRATEGI DAN EVALUASI KELOMPOK TERHADAP PENILAIAN STRATEGI DENGAN BALANCED SCORECARD - , Kiky Srirejeki ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This research examine whether managerâs involvement in the selection of strategic initiatives and evaluation systems affect the assessment of strategy with Balanced Scorecard (BSC). The research used experiment method and involved 47 students of Master of Accounting, Faculty of Economics and Business Universitas Gadjah Mada. The results of this study indicate that the manager who is involved in the selection of strategic initiatives and with those who do not involved will provide different support for assessment of strategic initiatives. These results are consistent with previous studies that indicate a bias of motivated reasoning. Furthermore, this study has not been able to provide empirical support that the group evaluation system can mitigate the bias of motivated reasoning.